Interventions to improve hearing aid use in adult auditory rehabilitation: A protocol for an updated systematic review and meta-analysis - Sian Calvert; Emma Elizabeth Broome; Mohamad Amin Pourhoseingholi; Jan W. Schoones; Jun Xia; Magdalena Sereda; Paul Bateman; Samuel MacKeith; Shihui Chen; Helen Henshaw (PLoS ONE, 2026)
Acquired hearing loss is common among adults, with hearing aids being the primary clinical management option. While hearing aids can improve communication and quality of life, many individuals do not use them consistently or at all. This article presents a protocol for an updated systematic review and meta-analysis of interventions aimed at improving or promoting long-term hearing aid use among adults with hearing loss who are fitted with at least one hearing aid. The review is guided by the Behaviour Change Wheel (BCW) and at its centre the COM-B model (Capability, Opportunity, Motivation – Behaviour), which suggests that the interaction of these three components influences behaviour. The BCW provides a comprehensive framework to understand how interventions target behaviour change and the mechanisms through which they operate. The review objective is to assess the effectiveness of interventions that aim to improve or promote hearing aid use among adults with acquired hearing loss who have at least one hearing aid. Understanding which intervention strategies are effective, and which behavioural functions they target, can help shape future research.